The Need for SMN-Independent Treatments of Spinal Muscular Atrophy (SMA) to Complement SMN-Enhancing Drugs - Hensel, Niko; Kubinski, Sabrina; Claus, Peter (Frontiers in Neurology, 2020)
Spinal Muscular Atrophy (SMA) is monogenic motoneuron disease caused by low levels of the Survival of Motoneuron protein (SMN). Recently, two different drugs for the treatment of the disease were approved. The antisense oligonucleotide Nusinersen/Spinraza® and the gene replacement therapy Onasemnogene Abeparvovec/Zolgensma® both enhance SMN-levels. These treatments result in impressive benefits for the patients. However, there is a significant number of non-responders and an intervention delay has a strong negative impact on efficacy. Obviously, later stages of motoneuron degeneration cannot be reversed by SMN-restoration. Therefore, complementary, SMN-independent strategies are needed which are able to address such SMN-irreversible degenerative processes. Those are defined as pathological alterations which are not reversed by SMN restoration for a given dose and intervention-delay. It is crucial to tailor SMN-independent approaches to the novel clinical situation with SMN-restoring treatments. On the molecular level, such SMN-irreversible changes become manifest in altered signaling modules as described by molecular systems biology. Based on our current knowledge about altered signaling, we introduce a network approach for an informed decision for the most potent SMN-independent treatment targets. Finally, we present recommendations for the identification of novel treatments which can be combined with SMN-restoring drugs.